(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to address the knowledge bases of strategic auditing and to indicate the role that it can play in improving the quality of the auditor’s report and improving the tax system, from linking the regular audit with the strategic audit in a way that serves the process of implementing and evaluating strategies and in a way that contributes to achieving the mission and objectives of the economic units on the one hand and maximizing their value on the one hand. On the other hand. The research was applied to a sample of administrators, accountants, auditors and evaluators working in the Iraqi General Tax Authority, for the data of the fiscal year 2021, and a questionnaire was designed in line with the objectives and hypotheses of the research and a set of appropriate statistical methods were used for that, and the research reached a set of conclusions that were from The most important of them is that the strategic audit can help improve the quality of the auditor’s report and develop the tax system